INTRODUCING ELECTROMAGNETIC ENERGY FROM HYDROCOLLOID WOUND DRESSING PASTE PENETRATING A GLASS BARRIER DISRUPTING HUMAN SKIN LIPID DROPLETS SIZE AND MEMBRANES: POSSIBLE IMPLICATIONS IN CANCER CELLS GENESIS AND/OR CURE - Embi, Abraham A. (International Journal of Research -GRANTHAALAYAH, 2023)
Prior publication demonstrated exogenous energy from a Hydrocolloid Wound Dressing strip had penetrated a 1 mm glass slide barrier slowing the evaporation of drops of water diluted Potassium Ferricyanide crystals of formula K3[Fe(CN6)]; and consequently, altering a human mini organ hair follicle metabolism. In that paper, a recommendation was made stating that “The introduction of exogenous non-biological material, namely a hydrocolloid wound dressing justified inclusion in future research protocols “In this manuscript, in vitro research is presented whereby harvested human skin lipid droplets were exposed also to a hydrocolloid wound dressing paste (HCWP) sandwiched between two glass slides (SDW). Results via microscopy images demonstrate the deleterious effect of the electromagnetic energy emitted by the HCWP, again documented penetrating a 1 mm glass on human skin lipid droplets membranes. Implications up to and including cancer genesis of this newly documented energy emission are unknown, although, it should be emphasized that the reprogramming of lipid metabolism is a hallmark of many cancers, including breast cancer. Additionally in 2016 electromagnetic energy emitted by the breakdown of H2O2 during cell respiration had been hypothesized to be a contributing factor in cancer genesis.